IMPLEMENTATION OF MINISTER OF RELIGION REGULATION NUMBER 19 OF 2018 ON THE EFFECTIVENESS OF MARRIAGE REGISTRATION IN BARRU DISTRICT, BARRU - Rais , Rahmi; Sukmiah (Meraja journal, 2024)
[Full Paper] to pdf Copyright (c) 2024 Meraja journal